Why some third age individuals develop entrepreneurial intentions: Exploring the psychological effects of posterity. (3rd May 2020) - Maalaoui, Adnane; Tornikoski, Erno; Partouche-Sebban, Judith; Safraou, Imen
ABSTRACT: This study attempts to enhance our understanding of why some third age individuals develop intentions toward entrepreneurship. Based on the theory of planned behavior and its three antecedents of entrepreneurial intentions, this study contributes to the literature on psychological drivers of entrepreneurship among older individuals. Our results among 204 French individuals between 45 and 65 years old showed that posterity positively moderates the relationship between entrepreneurial attitudes and entrepreneurial intentions, and negatively moderates the relationship between social norms related to the creation of new firms and entrepreneurial intentions. This study offers interesting insights concerning entrepreneurship among third age individuals.